2023
DOI: 10.3389/fimmu.2023.1148209
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1: a multi-faceted anti-inflammatory agent

Abstract: Inflammation contributes to many chronic conditions. It is often associated with circulating pro-inflammatory cytokines and immune cells. GLP-1 levels correlate with disease severity. They are often elevated and can serve as markers of inflammation. Previous studies have shown that oxytocin, hCG, ghrelin, alpha-MSH and ACTH have receptor-mediated anti-inflammatory properties that can rescue cells from damage and death. These peptides have been studied well in the past century. In contrast, GLP-1 and its anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 204 publications
0
24
0
Order By: Relevance
“…Obesity has been associated with chronic inflammation, and GLP-1RA can modulate these inflammatory processes ( 27 ). GLP-1R is present in macrophages, lymphocytes, and monocytes which regulate immune cell signaling by suppressing proinflammatory cytokines such as TNF-α, IL-6, and IL-1β ( 28 ).…”
Section: Molecular Mechanisms Of Semaglutide and Liraglutidementioning
confidence: 99%
“…Obesity has been associated with chronic inflammation, and GLP-1RA can modulate these inflammatory processes ( 27 ). GLP-1R is present in macrophages, lymphocytes, and monocytes which regulate immune cell signaling by suppressing proinflammatory cytokines such as TNF-α, IL-6, and IL-1β ( 28 ).…”
Section: Molecular Mechanisms Of Semaglutide and Liraglutidementioning
confidence: 99%
“…The early research has demonstrated that the level of plasma GLP-1 after oral carbohydrate ingestion is considerably decreased in obese patients in comparison to a lean group [ 194 ]. GLP-1, in addition to participating in glycemic control, has anti-inflammatory properties under many different conditions [ 195 ]. Given the fact that GLP-1R receptors are present in the respiratory tract, including airway smooth muscle cells, pulmonary vasculature, or type-II alveolar cells [ 193 ], GLP-1 may play an important role in the inflammatory processes associated with asthma.…”
Section: Peptides In Asthma–obesity Phenotypementioning
confidence: 99%
“…The interaction between the immune system and DKD has become increasingly evident, with kidney biopsies revealing accumulations of immune cells, notably macrophages and T-cells, and elevated levels of proinflammatory cytokines (TNF-alpha, MCP-1/CCL2, IL-6, IL-1β), orchestrated by NF-κβ [ 86 ]. This inflammatory cascade, fueled by high glucose levels and AGEs, activates pattern recognition receptors, leading to chronic inflammation and mitochondrial dysfunction, culminating in fibrosis and end-stage kidney disease [ 86 ]. GLP-1RAs have emerged as a significant counterforce, mimicking the effects of endogenous GLP-1 by activating GLP-1 receptors, which leads to a reduction in proinflammatory responses and direct beneficial impacts on kidney and vascular tissues.…”
Section: The Role Of Glp-1 Receptor Agonists In Renal Protection and ...mentioning
confidence: 99%